STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA MENTAL KEAGAMAAN SISWA DI MAN 1 JOMBANG - Muhammad Fahrur Rozi; Laily Masruroh (JURNAL ILMIAH NUSANTARA, 2025)
This article describes the strategies or methods of Islamic Religious Education Teachers in fostering the religious mentality of students at MAN 1 Jombang. This approach uses a qualitative approach with a type of phenomenological research. The technique in data collection is carried out using observation, interview, and documentation methods. The results of the study show that: 1) This study shows that the religious mentality of students at MAN 1 Jombang is good and will continue to develop. 2) Teacher's Strategy in Fostering Students' Religious Mentality, namely using a strategy of direct approach to students. 3) The supporting factor for the teacher's strategy in fostering the religious mentality of students is that many students are from previous madrasah graduates, so they already understand their obligation to be a student in obeying the rules of the madrasah, and as a devout Muslim in worship, the inhibiting factor is because the large number of students in the madrasah is sometimes difficult to manage them.